2017
DOI: 10.1080/17453674.2016.1275200
|View full text |Cite
|
Sign up to set email alerts
|

Different incidences of knee arthroplasty in the Nordic countries

Abstract: Background and purposeThe annual number of total knee arthroplasties (TKAs) has increased worldwide in recent years. To make projections regarding future needs for primaries and revisions, additional knowledge is important. We analyzed and compared the incidences among 4 Nordic countriesPatients and methodsUsing Nordic Arthroplasty Register Association (NARA) data from 4 countries, we analyzed differences between age and sex groups. We included patients over 30 years of age who were operated with TKA or unicom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 38 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…A recent study reported rises in incidence of knee arthroplasty across Nordic countries between 1997 and 2012 (Niemelainen et al. 2017 ). Moreover, the rate of hospital admissions due to knee and hip OA increased by 50% and 32% between 1998 and 2015 in Sweden ( http://www.socialstyrelsen.se ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported rises in incidence of knee arthroplasty across Nordic countries between 1997 and 2012 (Niemelainen et al. 2017 ). Moreover, the rate of hospital admissions due to knee and hip OA increased by 50% and 32% between 1998 and 2015 in Sweden ( http://www.socialstyrelsen.se ).…”
Section: Discussionmentioning
confidence: 99%
“… 45 This result is supported by the increasing incidence in younger TKA or UKA patients in the 2005 to 2015 period. 45 , 46 TKA and UKA revisions resulting from aseptic loosening and polyethylene wear/breakage are related to younger patients with high-level activity and participation in contact sports. The use of more ‘patient-specific’ new materials in accordance with the level of physical activity may help to reduce the risk of loosening in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) has been performed successfully to treat moderate to severe osteoarthritis. In the last decades, the number of TKAs and the prevalence of OA have increased severely and are expected to increase further because of obesity, older age and TKAs performed in younger patients [13]. Although TKA has demonstrated effectiveness with substantive and sustained improvement in quality of life, clinical performance in patients one year after TKA remains lower than for healthy adults [4].…”
Section: Introductionmentioning
confidence: 99%